A preliminary study of the occurrence of soil-transmitted helminths among standard one school children in urban and peripheral areas Kuantan, Pahang, Malaysia - Mohammad, Mardhiah; Mat Yusof, Afzan; Wan Azmi, Wan Nabilah (2014)
Soil-transmitted helminths or STHs are nematode that can infect human and causes soiltransmitted helminth infections (STHIs). In impoverished areas of the countries around the globe, STHI persists to infect mankind and cause a health burden especially among the school-aged children. These infections are classified as one of the seven most common neglected diseases. The nematodes that are responsible for STHIs are Ascaris lumbricoides, Trichuris trichiuria and two species of hookworm, namely Ancylostoma duodenale and Necator americanus. Favorable environment in Malaysia further augment the transmission of STHs. Hence, this epidemiological study is essential to provide latest data pertaining health status due to STHIs. Moreover, high numbers of related studies were done in 1970s and had decreasing since then. Furthermore, because STHIs were closely associated with poverty, poor sanitation and hygiene practice, lack information on STHs was available for the urban areas. Thus, this study aims to determine the occurrence of STHs from the stool of standard 1 school children at Sekolah Kebangsaan Bukit Goh and Sekolah Kebangsaan Bandar Indera Mahkota Utama. The objectives of the study are to detect A. lumbricoides, T. trichiuria and hookworms, to compare the occurrence of STHs between urban and peripheral areas and to investigate and identify the possible risk factors associated with STHIs. The stool samples obtained were processed by formal ether concentration technique and stained by giemsa and trichrome staining. From the study, generally, T. trichiuria was detected as the highest STHs. When the findings were stratified according to location of schools, A. lumbricoides and T. trichiuria had the highest occurrence in urban and peripheral areas, respectively. In addition, inadequate maternal education, low average family income, and poor hygiene especially did not cutting nails and washing fruits prior to consumption were the factors responsible for the occurrence of STH eggs among the infected children.